2015
DOI: 10.1186/s12911-014-0124-4
|View full text |Cite
|
Sign up to set email alerts
|

Early telemedicine training and counselling after hospitalization in patients with severe chronic obstructive pulmonary disease: a feasibility study

Abstract: BackgroundAn essential element in the treatment of patients with chronic obstructive pulmonary disease (COPD) is rehabilitation, of which supervised training is an important part. However, not all individuals with severe COPD can participate in the rehabilitation provided by hospitals and municipal training centres due to distance to the training venues and transportation difficulties. The aim of the study was to assess the feasibility of an individualized home-based training and counselling programme via vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 40 publications
(44 reference statements)
1
66
0
Order By: Relevance
“…The MAST model is currently the most widely used framework for evaluating telemedicine in the European Union and is used in a number of EU projects. Examples of MAST are available in studies by Minet et al [ 69 ] and Rasmussen et al [ 70 ].…”
Section: New Care and Business Models Tailored To Sustainability And mentioning
confidence: 99%
“…The MAST model is currently the most widely used framework for evaluating telemedicine in the European Union and is used in a number of EU projects. Examples of MAST are available in studies by Minet et al [ 69 ] and Rasmussen et al [ 70 ].…”
Section: New Care and Business Models Tailored To Sustainability And mentioning
confidence: 99%
“…Equality test has been traditionally considered difficult to perform on homomorphic encryption, because of its large circuit depth [ 7 , 15 , 16 ]. They evaluate the equality test on each encrypted tuple of database, so at least Ω ( n ) homomorphic operations are required for searching on database of size n .…”
Section: Methodsmentioning
confidence: 99%
“…For example, Cheon et al [ 6 ] presented a protocol to compute the edit distance on homomorphically encrypted data but it took about 27 s even on length 8 DNA sequence. It is not easy to efficiently approximate the edit distance over encryption even though the distance to a public human DNA sequence is given [ 7 ]. This inefficiency comes from the difficulty of homomorphic evaluation of equality test: Encrypting the inputs bit-wise and computing over the encrypted bits yield expensive computation cost (at least linear in the data bit-length).…”
Section: Introductionmentioning
confidence: 99%
“…Although telerehabilitation is promising in patients with cardiopulmonary diseases, clear evidence is still limited. It has been shown that supervised training and counselling patients at home may be associated with safety, feasibility and benefits for severe COPD patients [ 29 ]. Nevertheless, compared with usual pulmonary rehabilitation, no significant improvement was seen in COPD patients equipped with a tablet after 7–10 weeks of rehabilitation [ 30 ].…”
Section: Telerehabilitationmentioning
confidence: 99%